(untitled) (Proceedings of International Conference on Scientific Research in Natural and Social Sciences, 2024)
Diagnosis and treatment of malocclusion narrowing of the upper jaw is a challenge for dentists who are trying to correct this malocclusion at an early age. Patients with an can be diagnosed clinically and cephalometrically, but the diagnosis must be considered in the context of skeletal and dental structure. Accurate classification of this malocclusion narrowing of the upper jaw requires experience and training. Narrowing of the upper jaw malocclusion develops as a result of the interaction of many different etiological factors, including thumb and finger sucking, lip and tongue habits, airway obstruction, and true skeletal growth abnormalities. Treatment for narrowing of the upper jaw ranges from observation or simple habit control to complex surgical procedures. Successful identification of the etiology increases the chances of successful treatment.